Trends in flow intermittence for European rivers - Tramblay, Yves (2021)
Submitted by Teresa Albuquerque (teresal@ipcb.pt) on 2020-12-21T22:16:08Z No. of bitstreams: 1 Scopus_ Hydrological Sciences Journal.pdf: 159166 bytes, checksum: 796bb17c3ee15796face5d0dec7e34a7 (MD5)